Analysis Of Knowledge Of Wus Ages (15-49 Years Old) About Personal Hygiene With Incidence Of Leaching In The Krian Health Center, Sidoarjo Area, 2020 - Siti Julaichah; Riza Tsalatsatul Mufida (Journal for Research in Public Health, 2023)
The high rate of vaginal discharge in the Krian Sidoarjo Puskesmas area is due to many women of childbearing age who do not know about vaginal discharge so they consider vaginal discharge to be a normal and trivial matter, in addition to the shame when women experience vaginal discharge often makes women reluctant to consult a doctor. Research Objectives Analyzing the knowledge of women aged 15-49 years about peronal hygien with the occurrence of vaginal discharge in the Krian Public Health Center, Sidoarjo. Research methods using analytic methods with cross sectional approach. Sample using a sampling technique with stratified random sampling method, as many as 98 samples from the total population of women of childbearing age (15-49 years) of 4870 people. This study uses a questionnaire and data analysis using the Chi Square test. The results of the study based on the Chi Square test showed that the Statistical Test Results obtained a sig (2-tailed) value of 0.001 which indicates that the value is smaller than 0.05 so that the p value <α (0.05), then H1 is accepted. Conclusion from this study there is a relationship between knowledge of WUS about personal hygiene and the occurrence of vaginal discharge.